2006
DOI: 10.1111/j.1365-2125.2006.02833.x
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of phenylephrine for pseudoephedrine as a nasal decongeststant. An illogical way to control methamphetamine abuse

Abstract: The aim of this review was to investigate the rationale for replacing the nasal decongestant pseudoephedrine (PDE) with phenylephrine (PE) as a means of controlling the illicit production of methamphetamine. A literature search was conducted in electronic databases and use of textbooks. Restrictions have been placed on the sale of PDE in the USA in an attempt to control the illicit production of methamphetamine. This has caused a switch from PDE to PE in many common cold and cough medicines. PE is a poor subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…346,347 In fact, the efficacy of phenylephrine as an oral decongestant has not been well established. 345,348,349 Elevation of blood pressure after taking an oral decongestant is very rarely noted in normotensive patients and only occasionally in patients with controlled hypertension. However, because of variation in patient response, patients receiving oral decongestants should be followed for changes in blood pressure.…”
Section: Oral Decongestants [Summary Statements 70 71]mentioning
confidence: 98%
See 1 more Smart Citation
“…346,347 In fact, the efficacy of phenylephrine as an oral decongestant has not been well established. 345,348,349 Elevation of blood pressure after taking an oral decongestant is very rarely noted in normotensive patients and only occasionally in patients with controlled hypertension. However, because of variation in patient response, patients receiving oral decongestants should be followed for changes in blood pressure.…”
Section: Oral Decongestants [Summary Statements 70 71]mentioning
confidence: 98%
“…In an effort to reduce illicit production of methamphetamine, restrictions have been placed on the sale of pseudoephedrine in the United States. 345 This has promoted substitution of phenylephrine for pseudoephedrine in many OTC cold and cough remedies. However, phenylephrine, which appears to be less effective than pseudoephedrine, is extensively metabolized in the gut.…”
Section: Oral Decongestants [Summary Statements 70 71]mentioning
confidence: 99%
“…Pseudoephedrine (PSE) is an α-sympathomimetic vasoconstrictor given orally for the relief of nasal congestion. The efficacy and safety of PSE is proven and well established [18]. Aspirin  Complex is provided as a granule formulation in sachets.…”
Section: Aspirinmentioning
confidence: 99%
“…However, the efficacy of PE HCl 10-mg tablets-the recommended oral dose for adults and children (!12 years) for relief from nasal congestion-has been questioned. 16,18,19 A systematic review and meta-analysis of many of the studies that supported the original 1976 FDA labeling for nonprescription use of PE did not find that PE HCl 10 mg is effective in the treatment of nasal congestion. 20 A study showed that patients with seasonal allergic rhinitis (SAR) who were exposed to grass pollen in an environmental exposure unit and treated with a single dose of 12-mg PE HCl did not show a significant change from baseline in nasal congestion during a 6-hour evaluation period compared with patients treated with placebo in contrast to PDE 60 mg. 21 There was no statistically significant difference between PE HCl 10 mg and placebo in relieving nasal congestion in a second environmental exposure unit study in contrast to a combination of loratadine-montelukast.…”
mentioning
confidence: 97%
“…14,15 Accessibility to PDE has been limited in the United States since 2006 with the adoption of legislation calling for a comprehensive system of controls regarding the distribution and sale of drug products potentially used in the illicit production of methamphetamine. [16][17][18] Phenylephrine hydrochloride (PE HCl 10 mg) tablets, another oral decongestant, are marketed for OTC use in the United States for temporary relief from nasal congestion due to the common cold, hay fever, or other upper respiratory tract allergies, and for temporary relief from sinus congestion and pressure. However, the efficacy of PE HCl 10-mg tablets-the recommended oral dose for adults and children (!12 years) for relief from nasal congestion-has been questioned.…”
mentioning
confidence: 99%